2021
DOI: 10.1002/alz.057778
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcomes of anti‐amyloid‐β monoclonal antibodies in patients with Alzheimer's disease: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Background: For the last 20 years, the amyloid-beta (Aβ) cascade hypothesis has been dominant in the research of disease-modifying therapeutics, with spent of financial and clinical resources in potential drugs targeting Aβ peptide production or clearance. (1) In this context, monoclonal antibodies targeting beta-amyloid (Aβ-mAbs) are being tested to reduce the amyloid burden in patients with Alzheimer's Disease (AD). (2) However, the cognitive impact of Aβ-mAbs remains controversial. (3) We aim to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In (23). Other analyses did not estimate a cognitive benefit per amyloid change, but indicated either null effects or small benefits were plausible (6)(7)(8)(9)(10). None of these meta-analyses include the most recent data from CLARITY-AD (1) or GRADUATE I & II (unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In (23). Other analyses did not estimate a cognitive benefit per amyloid change, but indicated either null effects or small benefits were plausible (6)(7)(8)(9)(10). None of these meta-analyses include the most recent data from CLARITY-AD (1) or GRADUATE I & II (unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the CLARITY-AD trial rekindled discussion and debate on the value of reducing brain amyloid levels with amyloid-targeting drugs (1)(2)(3)(4). Previous meta-analyses of randomized trials of amyloid-targeting drugs suggested the effects of amyloid-removal on cognitive outcomes were close to null (5)(6)(7)(8)(9)(10), and these studies continue to be cited and referenced as evidence that an overall effect of this mechanism is likely to be negligible. Some have interpreted the small statistically significant effects reported in CLARITY-AD as unconvincing.…”
Section: Introductionmentioning
confidence: 99%
“…24 Other analyses did not estimate a cognitive benefit per amyloid change but indicated either null effects or small benefits were plausible. [7][8][9][10][11] None of these meta-analyses include the most recent data from CLARITY-AD, 1 GRADUATE I and II (unpublished), and TRAILBLAZER-ALZ 2. 5 Some researchers argue, based on qualitative assessment of the trials 40 and animal models, that amyloid removal has non-linear effects on cognition, with benefits only becoming apparent once a large fraction of amyloid has been removed.…”
Section: Discussionmentioning
confidence: 99%
“…included data from the phase II PRIME trial of aducanumab, one of the most optimistic trials of the benefits of amyloid removal to date (cognitive change per SUVR change), and obtained an estimate that indicated overall benefit 24 . Other analyses did not estimate a cognitive benefit per amyloid change but indicated either null effects or small benefits were plausible 7–11 . None of these meta‐analyses include the most recent data from CLARITY‐AD, 1 GRADUATE I and II (unpublished), and TRAILBLAZER‐ALZ 2 5…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD) has been historically known for its lack of effective treatments, despite decades of research. However, the FDA's approval of aducanumab as the first AD—modifying treatment in 2021, followed by approval of lecanemab in 2023, created significant hope among patients and speculation among providers (Abbott, 2022; Budd Haeberlein et al, 2022; Fernandez & Silva, 2021; Mahase, 2023). While most disease‐modifying treatments are perceived positively by the public and highly sought after, which individuals would seek a preventative treatment prior to a diagnosis is less widely understood.…”
Section: Introductionmentioning
confidence: 99%